PELABELAN GRACEFUL PADA GRAF LINTASAN Pn - Ramdhan Fazrianto Suwarman; Nur Inayah; Yanne Irene (UNIVERSITAS NEGERI MALANG, 2022)
A simple graph G=(V, E) with n vertices and m edges is called graceful, if that graph G can be labeled with a bijection f:V(G) 1, 2, .., n and g:E(G) 1, 2, .., m, with condition label on any edge equals the difference between the labels of the two endpoints. This study examined graceful labeling on path graph Pn for n>=3.